A hybrid artificial bee colony based on differential evolution for production scheduling problems. (23rd December 2014) - Wang, Hui; Wang, Wenjun; Zhao, Jia; Zhu, Huasheng; Sun, Hui
Artificial bee colony (ABC) is a new optimisation technique, which has been successfully applied to various optimisation problems. In this paper, we propose a new ABC algorithm called ABCDE, which utilises the differential evolution (DE) scheme. It is known that both employed and onlooker bees in ABC use the same solution search strategy to generate new candidate solutions. In our new approach ABCDE, the employed bees still use the original solution search strategy, while the onlooker bees employ the DE scheme. Experimental studies are conducted on a set of recently proposed CEC 2014 benchmark functions. Computational results show the good search abilities of ABCDE. To further verify the performance of ABCDE on discrete optimisation problems, we apply ABCDE to solve production scheduling problems. Simulation results demonstrate that our approach can achieve promising solutions.